Recognition and management of adults with Turner syndrome: From the transition of adolescence through the senior years. Issue 10 (16th August 2019) - Lin, Angela E.; Prakash, Siddharth K.; Andersen, Niels H.; Viuff, Mette H.; Levitsky, Lynne L.; Rivera‐Davila, Michelle; Crenshaw, Melissa L.; Hansen, Lars; Colvin, Mary K.; Hayes, Frances J.; Lilly, Evelyn; Snyder, Emma A.; et al.
Abstract: Turner syndrome is recognized now as a syndrome familiar not only to pediatricians and pediatric specialists, medical geneticists, adult endocrinologists, and cardiologists, but also increasingly to primary care providers, internal medicine specialists, obstetricians, and reproductive medicine specialists. In addition, the care of women with Turner syndrome may involve social services, and various educational and neuropsychologic therapies. This article focuses on the recognition and management of Turner syndrome from adolescents in transition, through adulthood, and into another transition as older women. It can be viewed as an interpretation of recent international guidelines, complementary to those recommendations, and in some instances, an update. An attempt was made to provide an international perspective. Finally, the women and families who live with Turner syndrome and who inspired several sections, are themselves part of the broad readership that may benefit from this review.